Examining income expectations in the college and early post-college periods: New distributional tests of rational expectations - Thomas F. Crossley; Yifan Gong; Todd R. Stinebrickner; Ralph Stinebrickner (Institute for Fiscal Studies (IFS), 2021)
Unique longitudinal probabilistic expectations data from the Berea Panel Study, which cover both college and early post-college periods, are used to examine young adults' beliefs about their future incomes. We introduce a new measure of the ex post accuracy of beliefs, and two new approaches to testing whether, ex ante, agents exhibit Rational Expectations. We show that taking into account the additional information about higher moments of individual belief distributions contained in probabilistic ex-pectations data is important for detecting types of violations of Rational Expectations that are not detectable by existing mean-based tests. Beliefs about future income are found to become more accurate as students progress through school and then enter the post-college period. Tests of Rational Expectations almost always reject for the in-school period, but the evidence against Rational Expectations is much weaker in the post-college period.
Keywords: D84; 330; Subjective Expectations; Rational Expectations; Test; Income Uncertainty